2011
DOI: 10.3109/10428194.2010.543717
|View full text |Cite
|
Sign up to set email alerts
|

Frontline treatment of follicular lymphoma with fludarabine, cyclophosphamide, and rituximab followed by rituximab maintenance: toxicities overcome its high antilymphoma effect. Results from a Spanish Cooperative Trial (LNHF-03)

Abstract: We assessed the efficacy of fludarabine, cyclophosphamide, and rituximab in combination (FCR) as frontline treatment in patients with follicular lymphoma (FL) followed by rituximab maintenance. Seventy-five untreated patients with FL received FCR followed by maintenance with rituximab 375 mg/m(2) weekly during 4 weeks and every 6 months for 2 years. The overall response rate was 100%, with 89% complete remission (CR) and 11% partial remission (PR). Molecular remission was observed in all but one patient. Only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 36 publications
0
7
1
Order By: Relevance
“…With mature follow‐up, our findings suggest that depth of response may predict duration of response. Similarly, other prospective studies examining a fludarabine‐based frontline regimen in indolent lymphoma have demonstrated high complete response rates which translated into prolonged response duration (Zinzani et al , ; Montoto et al , ; Tomas et al , ; Vitolo et al , ). A retrospective analysis of 536 patients with FL enrolled in the Groupe d'Etude des Lymphomes de l'Altude (GELA) GELF86 studies with 14·9 years of follow‐up reported that achieving a CR with first‐line therapy was associated with superior OS (Bachy et al , ).…”
Section: Discussionmentioning
confidence: 93%
“…With mature follow‐up, our findings suggest that depth of response may predict duration of response. Similarly, other prospective studies examining a fludarabine‐based frontline regimen in indolent lymphoma have demonstrated high complete response rates which translated into prolonged response duration (Zinzani et al , ; Montoto et al , ; Tomas et al , ; Vitolo et al , ). A retrospective analysis of 536 patients with FL enrolled in the Groupe d'Etude des Lymphomes de l'Altude (GELA) GELF86 studies with 14·9 years of follow‐up reported that achieving a CR with first‐line therapy was associated with superior OS (Bachy et al , ).…”
Section: Discussionmentioning
confidence: 93%
“…By contrast, Tomás et al . , evaluated the efficacy of six cycles of FCR (fludarabine 25 mg/m 2 IV × 3, cyclophosphamide 1 g/m 2 × 1, rituximab 375 mg/m 2 × 1) followed by rituximab maintenance and reported a CR rate of 78% after induction and 92% after maintenance, but an unacceptably high rate of haematological toxicities (69% grade 3–4 neutropenia with a significant number of opportunistic infections). This led to premature termination of the trial.…”
mentioning
confidence: 99%
“…In this issue of Leukemia and Lymphoma, Tomás et al have investigated the use of a fludarabine-based, rituximab-containing induction regimen followed by rituximab maintenance therapy in previously untreated patients with advanced follicular lymphoma [9]. Seventy-five patients were entered onto a prospective phase II study in which the planned treatment was six cycles of fludarabine, cyclophosphamide, and rituximab, followed by maintenance rituximab given at 6-month intervals for a total of 2 years of therapy.…”
mentioning
confidence: 99%